OPTIMASI PERBANDINGAN AIR DAN ENZIM DALAM PROSES PEMBUATAN GULA CAIR SAGU ASAL SORONG SELATAN: Water-Enzymes Ratio Optimization in The Process of Making Liquid Sago Sugar from South Sorong - Agief Julio Pratama; Mochamad Hasjim Bintoro Djoefrie; Agus Budiyanto; Muhammad Iqbal Nurulhaq (IPB University, 2022)
Sago is one of the plantation crops that has the potential to be developed as food and non food for the people of Indonesia. Sago as a high source of starch can be used for liquid sugar production. This study aims to get an optimal ratio between water and enzymes in the production of sago liquid sugar from South Sorong. The study was conducted at the Center for Research and Development of Post -Harvest Agriculture, Bogor. Experiments were arranged in the split split plot design with a complete random design (RAL). Comparison of water with sago starch as the main plot, the α-amylase enzyme as a plot child and the glucoamilase enzyme as a plot child. Research is divided into two experiments, (1) ratio of water and sago starch (2) comparison of enzymes and sago starch. The results showed the ratio of starch and water, the dose of the α-amylase enzyme and glucoamylase had an effect on the value of brix, color and total sugar levels in both types of sago. The ratio of starch and water 1 : 4 with the dose of α-amylase enzyme 1 ml/kg starch and the enzyme glucoamilase 1 ml/kg starch is an optimal condition for making liquid sugar from the Fasampe sago starch. The ratio of starch and water 1 : 4 with the dose of α-amylase enzyme 1.2 ml/kg of starch and the glucoamilase enzyme 1.2 ml/kg of starch is an optimal condition for making liquid sugar from Fafion sago starch. Fasampe sago starch have a better appearance of liquid sugar colors than Fafion sago starch. ABSTRAKSagu merupakan salah satu tanaman perkebunan yang memiliki potensi untuk dikembangkan sebagai bahan pangan dan non pangan bagi masyarakat Indonesia. Sagu sebagai sumber pati yang tinggi dapat dimanfaatkan untuk produksi gula cair. Penelitian ini bertujuan untuk mendapatkan perbandingan optimal antara air dan enzim pada produksi gula cair sagu asal Sorong Selatan. Penelitian dilakukan di Balai Besar Penelitian dan Pengembangan Pasca Panen Pertanian, Bogor. Percobaan disusun dalam rancangan split split plot dengan rancangan acak lengkap (RAL). Perbandingan air dengan pati sagu sebagai petak utama, enzim α-amilase sebagai anak petak dan enzim glukoamilase sebagai anak petak. Penelitian terbagi atas dua percobaan yaitu : (1) perbandingan air dan pati sagu serta (2) perbandingan enzim dan pati sagu. Hasil penelitian menunjukkan perbandingan pati dan air, dosis enzim α-amilase dan glukoamilase memberikan pengaruh terhadap nilai brix, warna dan kadar gula total pada kedua jenis sagu. Perbandingan pati dan air 1 : 4 dengan dosis enzim α-amilase 1 ml/kg pati dan enzim glukoamilase 1 ml/kg pati merupakan kondisi optimal untuk membuat gula cair dari sagu Fasampe. Perbandingan pati dan air 1 : 4 dengan dosis enzim α-amilase 1,2 ml/kg pati dan enzim glukoamilase 1,2 ml/kg pati merupakan kondisi optimal untuk membuat gula cair dari sagu Fafion. Jenis sagu Fasampe memiliki tampilan warna gula cair yang lebih baik dari sagu Fafion.